Peran Kawasan Ekonomi Khusus Mandalika Lombok Terhadap Pengembangan Ekonomi Lokal (PEL) - Masrun Masrun; Wahidin Wahidin; Titi Yuniarti; M. Firmansyah (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
Mandalika Special Economic Area (KEK) has resonated as a national priority tourism center. ITDC as the regional implementing operator is building various facilities in the region. The large investment in the Mandalika area is certainly encouraging as well as alarming. This research is to explore deeply by identifying various business opportunities that can be developed at Mandalika Lombok KEK and strategizing local economic development around the Mandalik area. So that the specific target in this study is to give birth to the Local Economic Development Model in Mandalika Lombok KEK. The research was conducted qualitatively, data obtained from: Literature And Field Data Study with informants interviewed: 1). Business actors around Mandalika KEK, 2). Tourism activists, 3). Academics in tourism. From the results of the study can be described as follows: (a). The economic condition of the people in and around mandalika kek showed an increase in income before the covid pandemic, but decreased during the pandemic, (b) The economic condition of UMK in and around Kek Mandalika showed an increase in income before the covid pandemic, but decreased during the pandemic, (c). Local Economic Development that can be applied with the Mandalika KEK, can be done with the development of clusters with PEL categories in the field of Tourism, Art Market, lodging services and Creative Industries